Psychological Content of Functional Method of Restoration of Motor Function of Patients with Ischemic Stroke Taking into Account their Psycho-Physiological Characteristics - Prymachok, Liudmyla (Psychological Prospects Journal, 2019)
The author of the article says that the most frequent and severe consequence of cerebral ischemic stroke is the disorder of the motor functions of the person. Characteristic feather is the polymorphism of motor disorders of patients with cerebral ischemic stroke. In this case, general for patients is only the loss or violation of arbitrary actions (in the cases of hemiparesis or hemiplezia). Other clinical symptoms are largely variable and depend on a certain extent of the size of affected area, also its localization. According to various authors, persistent disturbances of motor function are also observed in the first days after the disease (in 70–80 % of cases of patients who had the ischemic stroke).221–234 Taking into account the empirical results we have obtained, we have developed a «Functional method for the restoration of motor function of patients with ischemic stroke, taking into account their psycho-physiological features», based on the psychological principles of stepwise, sequencing and complexity, as well as on the maximum and adequate psychological impact of the rehabilitation therapist on the patient.It was emphasized that the main directions of psychotherapy and psycho-correction of patients who suffered from ischemic stroke are: assistance in the process of understanding the patients, his/her basic needs, motives, instructions, relationships; his/her internal conflicts and mechanisms of psychological protection; features of his/her behavior and emotional response, their adequacy and realism; correction of patients’ instructions; assistance in formulating and securing adequate forms of patients’ behavior based on personal achievements in the cognitive, motivational, and emotional spheres; promotion of positive motivation for recovery and increased activity in treatment at the behavioral level.